Therapeutic challenges posed by critical drug–drug interactions in cystic fibrosis. (October 2016) - Jordan, Cameron L.; Noah, Terry L.; Henry, Marianna M.
Summary: This review seeks to re‐introduce cystic fibrosis (CF) clinicians to the pharmacology of drug–drug interactions among medications commonly used in CF and provide a framework for understanding these interactions among medications outside the scope of this discussion. We here focus on drugs impacted by the cytochrome P‐450 (CYP450) enzyme system and on interactions involving antimicrobials, psychotropic medications, and cystic fibrosis transmembrane conductance regulator (CFTR) modulators. Particular attention is needed when prescribing rifampin, azole antifungals and the CFTR modulators, ivacaftor, and lumacaftor/ivacaftor, in combination with other medications. The complexities of these interactions provide a strong rationale for case management by pharmacists and pharmacologists as a routine part of CF care.Pediatr Pulmonol. 2016;51:S61–S70. © 2016 Wiley Periodicals, Inc.